Understanding the Secret of SARS-CoV-2 Variants of Concern/Interest and Immune Escape - Lou, Fuxing; Li, Maochen; Pang, Zehan; Jiang, Lin; Guan, Lin; Tian, Lili; Hu, Jiaming; Fan, Junfen; Fan, Huahao (Frontiers in Immunology, 2021)
The global pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), place a heavy burden to global public health. With the fast-spreading of SARS-CoV-2, more than 4000 variants have been reported. A growing number of variants, including B.1.1.7, B.1.427/429, B.1.351, B.1.617 and P.1, are spreading in countries and causing great concern. These epidemic variants have been reported to have potential immune escape and one or more mutations endow them worrisome epidemiologic, immunologic or pathogenic characteristics. This review introduces the latest research progress on SARS-CoV-2 variants of interest and concern, key mutation sites, and their effects on virus infectivity, mortality and immune escape. Moreover, we compared the effects of various clinical SARS-CoV-2 vaccines and convalescent sera on epidemic variants, and evaluated the effects of several neutralizing antibodies on epidemic variants. In the end, we also look forward to the prospect of SARS-CoV-2 mutation, immune escape and epidemic prevention strategies.